Cytotoxic T lymphocytes, chemokines and antiviral immunity. - Price, D; Klenerman, P; Booth, B; Phillips, R; Sewell, A (1999)
Evidence that CD8+ CTLs produce chemokines following engagement of viral antigens, and that MIP-1alpha is required for an inflammatory response to virus challenge, suggests that these molecules are key elements in the generation of effective antiviral immunity. Here, David Price and colleagues argue that the antigen-dependent release of chemokines by CTLs provides an elegant mechanism linking localization, amplification and coordination of the antiviral immune response to specific recognition of infected host cells beyond the confines of the lymphoid system.